2008
DOI: 10.1002/mc.20504
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear expression of epidermal growth factor receptor is a novel prognostic value in patients with ovarian cancer

Abstract: The epidermal growth factor receptor (EGFR) has previously been detected in the nucleus of cancer cells and primary tumors. We have reported that EGFR translocates from the plasma membrane to the nucleus. Accumulation of nuclear EGFR is linked to increased DNA synthesis and proliferation; however, the pathological significance of nuclear EGFR is not completely understood. Here, we sought to determine the predictive value of EGFR for the survival of ovarian cancer patients, through the examination of 221 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 19 publications
6
127
1
Order By: Relevance
“…S2A). To confirm further the nuclear location of EGFR/RHA complexes, sequential photosections of a nucleus were examined, and EGFR/RHA complexes were clearly detected in middle sections (i.e., planes [11][12][13][14] in both MDA-MB-468 and HeLa cells (Fig. S2 B and C).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…S2A). To confirm further the nuclear location of EGFR/RHA complexes, sequential photosections of a nucleus were examined, and EGFR/RHA complexes were clearly detected in middle sections (i.e., planes [11][12][13][14] in both MDA-MB-468 and HeLa cells (Fig. S2 B and C).…”
Section: Resultsmentioning
confidence: 93%
“…Nuclear EGFR has been demonstrated to contribute to cancer cell resistance to cetuximab and radiation treatment (5,6) and to be negatively correlated with overall survival of patients with multiple cancer types (7)(8)(9)(10)(11). Moreover, nuclear EGFR interacts with signal transducer and activator of transcription 3 (STAT3), signal transducer and activator of transcription 5A (STAT5A), E2F1, DNA-dependent protein kinase (DNA-PK), and proliferating cell nuclear antigen (PCNA) and plays important roles in cell transformation, proliferation, and DNA repair and replication (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…[21][22][23][24][25] Increased nuclear EGFR localization correlates with poor clinical outcome in patients with breast cancer, 26 oropharyngeal SCC 27 and ovarian cancer. 28 Recent reports have characterized a novel nuclear localization sequence in EGFR and its family members. [29][30][31] Furthermore, transport mechanisms for EGFR to the nucleus have been described previously.…”
Section: Egfr Targeted Antibodies: Discovery and Functionmentioning
confidence: 99%
“…21,24 Clinical studies have indicated that increased nEGFR expression is associated with poor prognosis. 25,26 The nuclear translocation of EGFR is initiated by ligandinduced endocytosis. 27 Endosome-associated EGFR is recognized by importin b in the cytoplasm and is then transported to the inner nuclear membrane (INM) via the INTERNET (integral trafficking from the ER to the nuclear envelope transport) mechanism.…”
Section: Introductionmentioning
confidence: 99%